Pengaruh Penerapan Teknologi Informasi terhadap Kinerja Aparatur Nagari dalam Pengelolaan Keuangan Nagari - Resfiana Resfiana (Faculty of Social Science, Universitas Negeri Padang, 2019)
Effect of Information Technology Application on Performance of Nagari Apparatus in Nagari Financial Management in Tanah Datar District. This research is motivated by an indication that there is a lack of knowledge and ability of the nagari apparatus in applying information technology in the process of nagari financial management. This study uses quantitative methods. The population of this study amounted to 600 people consisting of Wali Nagari, Secretary, Treasurer and five Heads of Nagari Affairs. The samples were 240 respondents which were determined based on Slovin formula with a significant level of 5%. Sampling using Multi Stage Random Sampling technique. The instrument of this research was questionnaire using the Likert scale measurement. The analysis of this study used multiple linear regression tests. The results of this study show that the benefit sub-variable has a significant effect on the performance of the nagari apparatus with the Adjust R Square value regression test of 0.093, the ease of use sub-variable has a significant effect on the performance of the nagari apparatus with Adjust R Square regression test results of 0.071 and together the sub-variables of utilization and ease of use have a significant effect on the performance of the nagari apparatus in the management of nagari finance in Tanah Datar District with the results of regression tests of Adjust R Square values ​​of 0.094